2016
DOI: 10.3390/electronics5030052
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Drift-Diffusion Simulation of GaAs p-i-n and Schottky-Barrier Photodiodes for High-Speed AIIIBV On-Chip Optical Interconnections

Abstract: Abstract:In this paper, we consider the problem of the research and development of high-speed semiconductor photodetectors suitable for operation as parts of on-chip optical interconnections together with the high-speed laser modulators based on the A III B V nanoheterostructures. This research is aimed at the development of the models and modelling aids designed for the simulation of carrier transport and accumulation processes taking place in on-chip photosensitive devices during the detection of subpicoseco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(68 reference statements)
1
10
0
1
Order By: Relevance
“…Carrier mobilities, and generation and recombination rates for the next instant are estimated after the solution of the Poisson's equation at the actual moment of time. In paper [21] we showed that the application of Gummel's method together with the explicit and upwind difference schemes allows for the reduction in consumption of computational resources, but requires a shorter time step than other approaches.…”
Section: Explicit Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Carrier mobilities, and generation and recombination rates for the next instant are estimated after the solution of the Poisson's equation at the actual moment of time. In paper [21] we showed that the application of Gummel's method together with the explicit and upwind difference schemes allows for the reduction in consumption of computational resources, but requires a shorter time step than other approaches.…”
Section: Explicit Techniquementioning
confidence: 99%
“…The following Dirichlet boundary conditions for Equations (1)-(6) are applied at ohmic and Schottky contacts in the case of fixed voltage mode [21]:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This drift is given by the transit time of the photogenerated electrons and holes across the depletion layer and is given by 23 0.25emτtr=Wbold-italicVbold-italicd where W is the width of the depletion layer, and V d denotes the drift velocity of the charge carriers. The drift velocity is given by 24 Vd=μ0.25emE where μ denotes the carrier mobility, and E is the incident electric field on the PD.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Drift-diffusion numerical simulation of conventional on-chip p-i-n, Schottky barrier and uni-travelling carrier (UTC) photodetectors demonstrated that their response time is restricted by semiclassical transport effects in A III B V semiconductor materials and exceeds several picoseconds for the most efficient structures [17,[19][20][21]. Such performance is not sufficient for the adequate detection of short optical pulses generated by the lasers-modulators.…”
Section: Introductionmentioning
confidence: 99%